Quercetin: A Natural Ally in Combating Breast Cancer - Wu ZY; Qiu KY; Gai YJ; Wu JH; Zhou BX; Shi QF (International Journal of Nanomedicine)
Zi-Yun Wu, Kang-Yu Qiu, Yan-Jun Gai, Jia-Hui Wu, Bo-Xuan Zhou, Qing-Feng Shi Department of Breast Disease Center, The First Affiliated Hospital of Nanchang University, The First Clinical Medical College of Nanchang University, Jiangxi Medical College, Nanchang, 330006, People’s Republic of ChinaCorrespondence: Bo-Xuan Zhou, Email zhoubx@ncu.edu.cn Qing-Feng Shi, Email A1169627331@163.comAbstract: Breast cancer is one of the most common cancers among women worldwide, exhibiting notably high incidence and mortality rates. Despite its high fatality, a comprehensive study that mechanism and treatment of herbal medicines has not yet been conducted. Quercetin, a natural flavonoid, exhibits multi-targeted therapeutic potential against breast cancer. The aim of this study is to investigate and assess the mechanism and treatment of quercetin in breast cancer. We collected articles published within five years using PubMed, Google Scholar, and Web of Science with “breast cancer” and “quercetin” as keywords. Correspondingly, a total of 272 relevant articles were retrieved. Quercetin exhibits multi-modal therapeutic potential in breast cancer through its ability to orchestrate diverse molecular mechanisms, particularly in TNBC, such as targeting IGF1/IGF1R pathway, PI3K/Akt/mTOR, Wnt/β-catenin, MAPK/ERK cascades, and PTEN promoter demethylation. Critically, quercetin demonstrates synergistic activity with chemotherapy by overcoming drug resistance and reducing toxicity. Its therapeutic efficacy arises from concurrently inducing apoptosis and inhibiting proliferation, migration, invasion and metastasis. This profile positions quercetin as a strategic agent against breast cancer’s complex pathophysiology, effectively disrupting breast cancer malignant progression.Keywords: quercetin, breast cancer, apoptosis, drug carrier, combination therapy